Where Have the Periods Gone? The Evaluation and Management of Functional Hypothalamic Amenorrhea - Marie Eve Sophie Gibson; Nathalie Fleming; Caroline Zuijdwijk; Tania Dumont (Galenos Yayincilik, 2020)
Functional hypothalamic amenorrhea (FHA) is a common cause of amenorrhea in adolescent girls. It is often seen in the setting of stress, weight loss, or excessive exercise. FHA is a diagnosis of exclusion. Patients with primary or secondary amenorrhea should be evaluated for other causes of amenorrhea before a diagnosis of FHA can be made. The evaluation typically consists of a thorough history and physical examination as well as endocrinological and radiological investigations. FHA, if prolonged, can have significant impacts on metabolic, bone, cardiovascular, mental, and reproductive health. Management often involves a multidisciplinary approach, with a focus on lifestyle modification. Depending on the severity, pharmacologic therapy may also be considered. The aim of this paper is to present a review on the pathophysiology, clinical findings, diagnosis, and management approaches of FHA in adolescent girls.